Dose and elasticity of demand for self-administered cocaine in rats. Issue 2 (April 2016) - Kearns, David N.; Silberberg, Alan
Abstract : The present experiment tested whether the elasticity of demand for self-administered cocaine in rats is dose-dependent. Subjects lever pressed for three different doses of intravenous cocaine – 0.11, 0.33, and 1.0 mg/kg/infusion – on a demand procedure where the number of lever presses required per infusion increased within a session. The main finding was that demand for the 0.11 mg/kg dose was more elastic than it was for the two larger doses. There was no difference in demand elasticity between the 0.33 and 1.0 mg/kg doses. These results parallel findings previously reported in monkeys. The present study also demonstrated that a within-session procedure can be used to generate reliable demand curves.